RENOUNCING ORIENTALISM: A CRITICAL STUDY OF MOHSIN HAMID’S THE RELUCTANT FUNDAMENTALIST IN AN OCCIDENTAL PERSPECTIVE - Sobia Rana; Dr. Umaima Kamran (International Journal of Contemporary Issues in Social Sciences, 2024)
This research aims to critically study the theoretical idea of Occidentalism in Mohsin Hamid’s The Reluctant Fundamentalist (2007) to understand the hatred of the fundamentalists for the Western socio-cultural, political, and economic system. The primary focus of the research is to analyze the core causes of extremists’ abhorrence, particularly of third world countries, in selected novels toward Western, particularly American, ideologies and policies such as hegemony, exceptionalism, imperialism, colonialism and globalization. This research paper, further, exclusively focuses on the Occidentalist attitude of main characters in the select novel to highlight the Western low moralities and superficial values that seem inacceptable to the deep rooted (extremist) society of the non-West. The purpose of selecting a non-western 9/11 fiction writer for data collection of this research is that it reflects real-life events through the main characters of the novel, and most importantly it explores the reaction of both Oriental and Occidental on 9/11 incident. For the theoretical and methodological approach, the study undergoes Occidentalism: The West in the Eyes of its Enemies (Buruma & Margalit, 2004), as the scholarship of the authors has a potential for analyzing the data of the present study and for decoding the key concepts of occidentalism in the manuscript. The research concludes after the data analysis that Mohsin Hamid’s novel seems to not only articulate the vigorous notion of the Occidentalist toward the West but also address the reasons for the hatred of the Orientals. In the light of the conclusion drawn, it is asserted that Mohsin Hamid’s selected novel is largely occidentalist in nature.